152k views
0 votes
Please help and show how you got the answer:

4 - 6n = 60 - 2n

-7 + 11p = 3p - 47

3a - 28 - 7a = 10a

17 - 5r + 9r = 12 + 6r - 1

8 (y - 7) = -2 (y + 3)

-3 (8k + 5) = 3 (9 - k)

2 (3v - 5) = 2 (v - 11) - 4

-2/3 (15x + 3) -3x - 9

3 (1 - 9a) + 22a = 2( 2a - 9) - 15

-3 (3m - 10) - 7 = -5 (m + 1) + 3m

User Jrosell
by
5.0k points

1 Answer

3 votes

4 - 6n = 60 - 2n subtract 4 from both sides

-6n = 56 - 2n add 2n to both sides

-4n = 56 divide both sides by (-4)

n = - 14


-7 + 11p = 3p - 47 add 7 to both sides

11p = 3p - 40 subtract 3p from both sides

8p = -40 divide both sides by 8

p = - 5


3a - 28 - 7a = 10a combine like terms

(3a - 7a) - 28 = 10a

-4a - 28 = 10a add 28 to both sides

-4a = 10a + 28 subtract 10 from both sides

-14a = 28 divide both sides by (-14)

a = - 2


17 - 5r + 9r = 12 + 6r - 1 combine like terms

17 + (-5r + 9r) = (12 - 1) + 6r

17 + 4r = 11 + 6r subtract 17 from both sides

4r = -6 + 6r subtract 6r from both sides

-2r = -6 divide both sides by (-2)

r = 3


8(y - 7) = -2(y + 3) use distributive property: a(b + c) = ab + ac

(8)(y) + (8)(-7) = (-2)(y) + (-2)(3)

8y - 56 = -2y - 6 add 56 to both sides

8y = -2y + 50 add 2y to both sides

10y = 50 divide both sides by 10

y = 5


-3(8k + 5) = 3(9 - k) use distributive property: a(b + c) = ab + ac

(-3)(8k) + (-3)(5) = (3)(9) + (3)(-k)

-24k - 15 = 27 - 3k add 15 to both sides

-24k = 42 - 3k add 3k to both sides

-21k = 42 divide both sides by (-21)

k = -2


2(3v - 5) = 2(v - 11) - 4 use distributive property: a(b + c) = ab + ac

(2)(3v) + (2)(-5) = (2)(v) + (2)(-11) - 4

6v - 10 = 2v - 22 - 4

6v - 10 = 2v - 26 add 10 to both sides

6v = 2v - 16 subtract 2v from both sides

4v = -16 divide both sides by 4

v = -4


-2/3 (15x + 3) -3x - 9 use distributive property: a(b + c) = ab + ac

= (-2/3)(15x) + (-2/3)(3) - 3x - 9

= (-2)(5x) - 2 - 3x - 9

= -10x - 2 - 3x - 9 combine like terms

= (-10x - 3x) + (-2 - 9)

= -13x - 11


3(1 - 9a) + 22a = 2(2a - 9) - 15

use distributive property: a(b + c) = ab + ac

(3)(1) + (3)(-9a) + 22a = (2)(2a) + (2)(-9) - 15

3 - 27a + 22a = 4a - 18 - 15 combine like terms

3 + (-27a + 22a) = 4a + (-18 - 15)

3 - 5a = 4a - 33 subtract 3 from both sides

-5a = 4a - 36 subtract 4a from both sides

-9a = -36 divide both sides by (-9)

a = 4


-3(3m - 10) - 7 = -5(m + 1) + 3m

use distributive property: a(b + c) = ab + ac

(-3)(3m) + (-3)(-10) - 7 = (-5)(m) + (-5)(1) + 3m

-9m + 30 - 7 = -5m - 5 + 3m combine like terms

-9m + (30 - 7) = (-5m + 3m) - 5

-9m + 23 = -2m - 5 subtract 23 from both sides

-9m = -2m - 28 add 2m to both sides

-7m = -28 divide both sides by (-7)

m = 4

User PSCampbell
by
5.9k points